Oral History Program Interview: Lillie Eva Grose May - May, Lillie Eva Grose
Born in Wright City, McCurtain County, Oklahoma in 1918, May and her family would later land in Shafter, California on December 11, 1931. The interview includes her family's perspectives on welfare, her thoughts on The Grapes of Wrath's characterization of destitute migrants, the de facto segregation placing demographic groups into "colonies," how "Okie" is a derogatory term pertaining to a people with nothing, prejudice in the classroom, and the living situation in the Hoover camp on Jewett street near Chester Ave.